2021
DOI: 10.2147/ott.s278710
|View full text |Cite
|
Sign up to set email alerts
|

TCEB3 is Regulated by Circ-0000212/miR-140-3p Axis to Promote the Progression of Cervical Cancer

Abstract: Background Cervical cancer is a common female malignancy, which accounts for a large proportion of cancer-related mortality in the world. Therefore, exploring the mechanisms of cervical cancer progression and seeking new therapeutic targets are extraordinarily needful. The aim of this study was to explore the role of TCEB3 in cervical cancer progression. Methods TCEB3 expression was detected in cervical cancer tissue and adjacent normal tissues using qRT-PCR and immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…At the same time, more and more studies have shown that circRNA plays a key role in cervical cancer tumorigenesis. In this study, circ_0000212 was enhanced in cervical cancer, consistent with the study of Wang et al [28]. As we have seen, the Cancer Genome Atlas (TCGA) database also exhibited that circ-0000212 expression was upregulated in cervical cancer tissues [28].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…At the same time, more and more studies have shown that circRNA plays a key role in cervical cancer tumorigenesis. In this study, circ_0000212 was enhanced in cervical cancer, consistent with the study of Wang et al [28]. As we have seen, the Cancer Genome Atlas (TCGA) database also exhibited that circ-0000212 expression was upregulated in cervical cancer tissues [28].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, circ_0000212 was enhanced in cervical cancer, consistent with the study of Wang et al [28]. As we have seen, the Cancer Genome Atlas (TCGA) database also exhibited that circ-0000212 expression was upregulated in cervical cancer tissues [28]. In addition, circ_0000212 has been implied to facilitate cell proliferation in colorectal cancer [16].…”
Section: Discussionsupporting
confidence: 90%
“…Functionally, we revealed the growth‐ and metastasis‐promoting role of ELOA, supporting ELOA as a candidate oncogene in GC. Wang et al reported that ELOA promotes cancer progression in cervical cancer, 9 whereas we recently revealed a tumor suppressive role of ELOA in CRC 8 . These studies suggested that ELOA exerts different functions in different cancer types, and the potential mechanisms explaining the variable roles of ELOA in different cancers should be further elucidated.…”
Section: Discussionmentioning
confidence: 60%
“…We previously revealed that ELOA transcriptionally activates LHPP expression and inhibits tumorigenesis and metastasis in colorectal cancer (CRC) 8 . Interestingly, a recent study reported that ELOA promotes the progression of cervical cancer 9 . However, whether and how ELOA affects tumorigenesis in GC remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…A549) Kong et al ( 2015 ) Down BLCA tissues and four cell lines (i.a. T24) Yuan et al ( 2021 ) Down BRCA tissues stage I-IV Dou et al ( 2021 ) Down BRCA tissues, MCF-7 (ER + ) and MDA-MB-453 (HER2 + ) Zhou et al ( 2019 ) Down HCC tissues Gao et al ( 2021b ) Down CeCa tissues Wang et al ( 2022a ) Down CeCa tissues Wang et al ( 2021g ) Down OVCA tissues Qiao et al ( 2021 ) † , ‡ For description see footnote to Table 2 …”
Section: Mirnas Targeting Tyms Mrnamentioning
confidence: 99%